TOPIC DEVELOPMENT AND THEMATIC PATTERNS FOR THE INDONESIAN TEXT OF FRIDAY SERMONS - Sukarno . (Humaniora, 2014)
This article is a part of the research result conducted in Jember, East Java, about metafunctions, register, and generic structures of Friday sermon texts. The focus of this article is the techniques of topic development through thematic patterns as one of the realizations of textual meanings. The data of the research were collected by recording four different khatib’s (preacher’s) speeches in four different Friday sermons through participatory observations in January, February, and September 2012. The recorded data were transcribed into a written text called Friday sermon texts (FSTs). Next, the data were analyzed to study the topic development in the clause complex level, in the paragraph level, and in the text level. The result of the research shows that the topics in Friday sermon texts in the clause levels were developed through three thematic patterns, namely: Pattern 1: Theme-Theme, Pattern 2: Theme-Rheme-Theme, and Pattern 3: Theme-Theme-Rheme-Theme. The development of the topics in the paragraph level is done mainly by a deductive method, that is by placing a Hyper-theme in the initial position of the paragraph. In the text level, the topic discussion is developed through Macro-theme and Macro-rheme structure, in which the Macro-themes mostly occupy the beginnings of the texts, namely: the first paragraph (FST 3), the second paragraph (FST 1 and 4) and the third paragraph (FST 2). In addition to be the device for developing the topics, thematic patterns also contribute to build a coherent text.